Structural Changes Observed in the Piriform Cortex in a Rat Model of Pre-motor Parkinson’s Disease - Sancandi, Marco; Schul, Emma Victoria; Economides, Georgia; Constanti, Andrew; Mercer, Audrey (Frontiers in Cellular Neuroscience, 2018)
Early diagnosis of Parkinson’s disease (PD) offers perhaps, the most promising route to a successful clinical intervention, and the use of an animal model exhibiting symptoms comparable to those observed in PD patients in the early stage of the disease, may facilitate screening of novel therapies for delaying the onset of more debilitating motor and behavioural abnormalities. In this study, a rat model of pre-motor PD was used to study the aetiology of hyposmia, a non-motor symptom uniquely linked to the early stage of the disease when the motor symptoms have yet to be experienced. The study focussed on determining the effect of a reduction of both dopamine and noradrenaline levels on the olfactory cortex. Neuroinflammation and striking structural changes were observed in the model. These changes were prevented by treatment with a neuroprotective drug, a glucagon-like peptide-1 (GLP1) receptor agonist, exendin-4 (EX-4).